Genetic Characterization of Mycobacterium Tuberculosis Isolated from Captive Zoo Animals - Soni, Payal; Singh, Jitendra; Vimal, Bhartendu; Kumar, Manoj; Lokhande, Leena; Gupta, Anvita Malhotra; Shrivas, Arti; Maurya, Anand Kumar; Purwar, Shashank; Singh, Sarman (EcoHealth, 2025)
Zoonotic tuberculosis is a neglected subject that has the potential to impede the effectiveness of the TB elimination program. The present study aimed to determine the genetic diversity and drug resistance in the Mycobacterium tuberculosis isolates from captive wild animals. A total of 67 tissue samples were collected from 33 animals, comprising 21 wild captive animals from various species and 12 slaughtered domestic buffaloes. These samples were subjected to the detection of Mycobacterial species by culture isolation, and further molecular identification by mPCR, Xpert-Ultra and TrueNat MTB/Rif assay; followed by drug susceptibility profiling by MTBDRplus and Spoligotyping of the isolates. Of the 67 samples from captive zoo animals, 44 samples were culture positive. Of these, 38 isolates were identified as Mycobacterium tuberculosis Complex (MTBC) and remaining 6 were identified as non- tuberculous mycobacteria (NTM). All NTM isolates were from different tissues of a Tigress which also had mixed infection with MTBC. All the 38 culture isolates were further subjected to phenotypic drug susceptibility testing (pDST) and genotyping. Twenty-eight (73.69%) of them, were pan-susceptible, 9 (23.68%) exhibited isoniazid mono-resistance, and 1 (2.63%) was rifampicin mono-resistant. On genotyping, 27 (71.05%) of the samples were classified as 'Orphan'. Ten (26.32%) isolates were identified as CAS1_DELHI, clustered within SIT number 375, while one sample (2.63%) remained unidentified. The drug resistance and genotyping patterns were similar to the human population. Our results show that M. tuberculosis was major cause of Zoonotic TB and should be considered as potential reverse zoonotic agent in India.